Can Diffusion-Weighted Imaging and Related Apparent Diffusion Coefficient be a Prognostic Value in Women With Breast Cancer?. (7th February 2017) - Rabasco, Paola; Caivano, Rocchina; Simeon, Vittorio; Dinardo, Giuseppina; Lotumolo, Antonella; Gioioso, Matilde; Villonio, Antonio; Iannelli, Giancarlo; D'Antuono, Felice; Zandolino, Alexis; Macarini, Luca; Guglielmi, Giuseppe; et al.
ABSTRACT: Purpose : To analyze diffusion-weighted imaging (DWI) and the related apparent diffusion coefficient (ADC) in women with breast cancer, correlating these values with the presence at 3 years of distant metastases, and to demonstrate that DWI-Magnetic Resonance Imaging (MRI) and related ADC values may represent a prognostic value in the study of women with breast cancer. Materials and methods : Sixty women (aged 45–73 years) affected with breast cancer with a follow-up in 3 years were enrolled. On DWI, we obtained the ADC values, and these were correlated with the clinical condition of patients at 3 years. Moreover, tumour size, lymph node status, and molecular markers, including estrogens receptor, progesterone receptor, Ki-67 index, and human growth factor receptor 2 protein, were correlated with ADC values. This study was approved by the Scientific Committee of our institution. Results : We considered patients with metastasis at 3 years (12 patients – 20%) and without metastasis (48 patients – 80%). The mean ADC value in patients with no metastases at 3 years was 1.06 ± 0.38, while for patients with metastases it was 0.74 ± 0.34 ( p = .011). The receiver–operator curve analysis identified a value of 0.75 (<0.75 with risk to develop metastasis) as the best predictive cutoff for ADC values, with the highest sensitivity (81.25%) and higher specificity (66.67%). After regression analysis, ADC value, positivity to estrogen–progestin receptors, and presence of lymph nodes were the only prognostic factors found to be statistically significant. Conclusions : DWI-MRI and related ADC values may represent a prognostic value in women with breast cancer.